Change of activity of enzymes in blood of patients with multiple sclerosis depending on the type of disease - O. Markovska (Kazimierz Wielki University, 2017)
A study was made of the dynamics of changes in the activity of membrane-bound enzymes in the blood of 110 patients with multiple sclerosis, depending on the type of disease course. It was established that in patients with multiple sclerosis there is persistent disfermentemia, severity and directivity, which depends on the type of the course of multiple sclerosis. The most pronounced enzymatic imbalance is observed in the primary-progressive type of multiple sclerosis, which is a marker of deeper disturbance of metabolic, oxidation-reduction and energy processes in cells due to the steady progression of the disease. The revealed correlation dependences of the content of the studied enzymes in the remitting type of MS flow to the stage of exacerbation indicate the pathogenetic and diagnostic significance of these indices, which makes it possible to use them as additional markers ofМS flow activity. Decrease in the level of сreatine phosphokinase in all types of disease course, reflects the degree of decrease in metabolic and energy processes in muscle and neural tissue cells, possibly due to the development of motor disorders.